Xiangbinfang granules enhance gastric antrum motility via intramuscular interstitial cells of Cajal in mice - Chen, Qi-Cheng (World J Gastroenterol, 2021)
BACKGROUND: Interdigestive migrating motor complexes (MMC) produce periodic contractions in the gastrointestinal tract, but the exact mechanism of action still remains unclear. Intramuscular interstitial cells of Cajal (ICC-IM) participate in gastrointestinal hormone and neuromodulation, but the correlation between ICC-IM and MMC is also unclear. We found that xiangbinfang granules (XBF) mediated the phase III contraction of MMC. Here, the effects of XBF on gastric antrum motility in W/W(v) mice and the effects of ICC-IM on gastric antrum MMC are reported. AIM: To observe the effects of ICC-IM on gastric antrum motility and to establish the mechanism of XBF in promoting gastric antrum motility. METHODS: The density of c-kit-positive ICC myenteric plexus (ICC-MP) and ICC-IM in the antral muscularis of W/W(v) and wild-type (WT) mice was examined by confocal microscopy. The effects of XBF on gastric antrum slow waves in W/W(v) and WT mice were recorded by intracellular amplification recording. Micro-strain-gauge force transducers were implanted into the gastric antrum to monitor the MMC and the effect of XBF on gastric antrum motility in conscious W/W(v) and WT mice. RESULTS: In the gastric antrum of W/W(v) mice, c-kit immunoreactivity was significantly reduced, and no ICC-IM network was observed. Spontaneous rhythmic slow waves also appeared in the antrum of W/W(v) mice, but the amplitude of the antrum slow wave decreased significantly in W/W(v) mice (22.62 ± 2.23 mV vs 2.92 ± 0.52 mV, P < 0.0001). MMCs were found in 7 of the 8 WT mice but no complete MMC cycle was found in W/W(v) mice. The contractile frequency and amplitude index of the gastric antrum were significantly increased in conscious WT compared to W/W(v) mice (frequency, 3.53 ± 0.18 cpm vs 1.28 ± 0.12 cpm; amplitude index, 23014.26 ± 1798.65 mV·20 min vs 3782.16 ± 407.13 mV·20 min; P < 0.0001). XBF depolarized smooth muscle cells of the gastric antrum in WT and W/W(v) mice in a dose-dependent manner. Similarly, the gastric antrum motility in WT mice was significantly increased after treatment with XBF 5 mg (P < 0.05). Atropine (0.1 mg/kg) blocked the enhancement of XBF in WT and W/W(v) mice completely, while tetrodotoxin (0.05 mg/kg) partially inhibited the enhancement by XBF. CONCLUSION: ICC-IM participates in the regulation of gastric antrum MMC in mice. XBF induces MMC III-like contractions that enhance gastric antrum motility via ICC-IM in mice.